2019
DOI: 10.1080/00273171.2019.1616526
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Reliability and Replicability of Psychopathology Network Characteristics

Abstract: Acknowledgements: Thanks to Nicholas R. Eaton and Eiko I. Fried for comments on an earlier version of this manuscript. Thanks also to Fried and colleagues-who authored the study on the replicability of posttraumatic stress disorder symptom networks (Fried et al., 2018, Clin Psychol Sci)-for making their summary data, output, and code available, and for encouraging reanalysis of the data for further replicability research. AbstractPairwise Markov random field networks-including Gaussian graphical models (GGMs) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 50 publications
1
89
1
Order By: Relevance
“…While it may be naive to expect exact replication, observed levels of inconsistency between networks seem particularly problematic in the context of a theory that emphasizes interpretation of the presence, absence, strength and sign of each individual edge and the corresponding centrality of individual symptoms. Importantly, optimistic perspectives on the reliability and replicability of symptom networks are often based on methods (e.g., bootnet, the omnibus NetworkComparisonTest, and correlations between lists of edges) that shift the focus away from these detailed features, and towards global network patterns that do not correspond with the basis of network theory or the insights that symptom networks have been promoted to provide. The result is that these popular methods create an impression of reliability and replicability that fails to translate to the level at which networks are interpreted.…”
mentioning
confidence: 99%
“…While it may be naive to expect exact replication, observed levels of inconsistency between networks seem particularly problematic in the context of a theory that emphasizes interpretation of the presence, absence, strength and sign of each individual edge and the corresponding centrality of individual symptoms. Importantly, optimistic perspectives on the reliability and replicability of symptom networks are often based on methods (e.g., bootnet, the omnibus NetworkComparisonTest, and correlations between lists of edges) that shift the focus away from these detailed features, and towards global network patterns that do not correspond with the basis of network theory or the insights that symptom networks have been promoted to provide. The result is that these popular methods create an impression of reliability and replicability that fails to translate to the level at which networks are interpreted.…”
mentioning
confidence: 99%
“…Partial vs. zero-order correlations. In Forbes et al (2019), the above model was suggested to have inherent limitations that contribute to unreliable findings compared to, say, zero-order correlations ξ ij = F (r ij ) ("association networks"). The key difference is that zero-order correlations are not conditioned on any variables and partial correlations are conditioned on k − 2 variables.…”
Section: The Gaussian Graphical Modelmentioning
confidence: 99%
“…The key difference is that zero-order correlations are not conditioned on any variables and partial correlations are conditioned on k − 2 variables. Although not mentioned in Forbes et al (2019), controlling for variables does present two underappreciated hurdles for evaluating replicability:…”
Section: The Gaussian Graphical Modelmentioning
confidence: 99%
“…Some have argued that network interpretations and clinical implications focus on the presence, sign, and strength of specific edges and the rankorder of node centrality (i.e., which symptom is most central, second most central, third most central, etc.). An examination of these characteristics within and across two samples of Major Depressive Disorder (MDD) and Generalized Anxiety Disorder (GAD) symptoms revealed that 83.4-86.6% of edges replicated within and between networks but only 16.7-55.6% of individual nodes' centrality rank-order matched within and between samples (Forbes et al, 2017a), leading to the conclusion that "popular network analysis methods produce unreliable results" (Forbes et al, 2017a; see also Forbes, Wright, Markon, & Krueger, 2019). 2 2 Steinley, Hoffman, Brusco, and Sher (2017) provided a commentary on Forbes et al's (2017a) paper in which they introduced a new method termed fixed-margin sampling for examining whether network model results differ from what would be expected by chance.…”
Section: Replicability and Generalizability Of Cross-sectional Psychomentioning
confidence: 99%